El mundo persa y las adiciones griegas en el libro de Esther (Argos, 2025)
No other book of the Old Testament has received such mixed reviews as the Book of Esther. This work describes the origins of the Jewish feast of Purim in a Persian background: the king Asuero (Xerxes), the court, the harem, wealth, banquets, royal costume, but makes no reference to the God of Israel, to the practices and beliefs of Judaism, to the national history of the Jewish people. The Greek version (Septuagint) contains six major additions and a colophon over and above the Hebrew text. This paper deals with the singular characteristics of the book: a cultural convergence of Persian, Greek and Jewish worlds.
Keywords: Esther; Persian world; Greek additions; history; fiction